2017
DOI: 10.12659/msm.901055
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin Growth Factor 1 Protects Neural Stem Cells Against Apoptosis Induced by Hypoxia Through Akt/Mitogen-Activated Protein Kinase/Extracellular Signal-Regulated Kinase (Akt/MAPK/ERK) Pathway in Hypoxia-Ishchemic Encephalopathy

Abstract: BackgroundInsulin growth factor 1 (IGF-1) is reported to modulate cell growth and acts as potential therapy for traumatic brain injury. This study was designed to investigate the effect of IGF-1 on hypoxia-induced apoptosis in neural stem cells (NSCs).Material/MethodsA hypoxia model was constructed using NSCs separated from the hippocampus of rat. NSCs were divided into four groups: cells under normoxic conditions that acted as controls (C group), cells under hypoxia (H group), cells under hypoxia with IGF-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
3
17
1
Order By: Relevance
“…Our analysis confirmed that AKT phosphorylation, which decreased in hypoxic condition, is recovered by GH treatment, while Bcl2 expression increases in response to GH. In addition, we found that although these were not statistically significant, the absolute levels of phosphorylated AKT and Bcl2 expression increased with the IGF-1 treatment, which is consistent with the numerous evidence, indicating that IGF-1 is an activator of the PIK3/AKT signaling pathway as a mechanism to promote cell survival and inhibit apoptosis [ 14 , 20 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our analysis confirmed that AKT phosphorylation, which decreased in hypoxic condition, is recovered by GH treatment, while Bcl2 expression increases in response to GH. In addition, we found that although these were not statistically significant, the absolute levels of phosphorylated AKT and Bcl2 expression increased with the IGF-1 treatment, which is consistent with the numerous evidence, indicating that IGF-1 is an activator of the PIK3/AKT signaling pathway as a mechanism to promote cell survival and inhibit apoptosis [ 14 , 20 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our results observed that a large number of apoptotic neurons in VD model rats, while SalB prevented apoptosis of hippocampal neurons in CA1 region in VD model rats. It has been shown that IGF-1 increased cell viability while decreasing apoptosis [36]. Our research suggest that SalB inhibited apoptosis of hippocampal neurons in VD model rats maybe through enchancing hippocampal IGF-1 expression.…”
Section: Discussionmentioning
confidence: 50%
“…PI3K/Akt-GSK3β signaling contributes to neuronal growth, proliferation, and differentiation of NSCs [61]; promotes hippocampal neurogenesis in a mouse model of Alzheimer’s disease [62]; and ameliorates the apoptosis of neuronal cells in a rat model of Parkinson’s disease [63]. ERK1/2 is a key regulator for neural differentiation [64], modulates neurogenesis [65] and neural apoptosis [66], and improves depression-like behaviors [67]. Activation of ERK and Akt pathways protected PC12 cells against oxidative stress [68], and MG53 activated PI3K/Akt-GSK3β and ERK1/2 signaling to elicit cardioprotective functions [15, 22].…”
Section: Discussionmentioning
confidence: 99%